On the employment model of Japanese women - I. P. Lebedeva (Ежегодник Япония, 2019)
An increasing number of Japanese women are joining the economy, but the Japanese labor market is still more friendly to men than to women. Although much has been done in recent years in terms of creating conditions for a fuller participation of women in the economic life of the country, in general, their employment model has not undergone major changes. It is more difficult for women than for men to get a position of regular worker, in terms of working conditions (salary level, opportunities for professional growth, job content, etc.) they are in a worse position than men. As before, due to the harsh conditions of lifetime employment, many female regular employees of Japanese firms after a child’s birth interrupt their careers, and returning to the labor market after a few years, they prefer to take jobs as non-regular workers. Housekeeping and childcare are also still mainly entrusted to women. The “glass ceiling” that Japanese women, making a career, clash with, “1 million yen wall” that pushes women into a non-regular employment zone - these are also today’s realities. The situation in the field of female employment has become one of the main factors of the emergence of a number of painful social phenomena, such as a reduction of the number of marriages, an increase in the share of unmarried young women, in the age of first marriage and first child birth, a decrease in the number of children in a family and fertility rate, etc. Meanwhile, perhaps the main reason for the preservation of the situation in the field of women’s employment is that ideas about the separation of the roles of women and men in the family, society, and at work are widespread in society, including among the Japanese women themselves. Therefore, it seems that it will take quite a long time till real changes become tangible.